2019
DOI: 10.1111/1751-7915.13388
|View full text |Cite
|
Sign up to set email alerts
|

Dismantling the bacterial virulence program

Abstract: Summary In the face of rising antimicrobial resistance, there is an urgent need for the development of efficient and effective anti‐infective compounds. Adaptive resistance, a reversible bacterial phenotype characterized by the ability to surmount antibiotic challenge without mutation, is triggered to cope in situ with several stressors and is very common clinically. Thus, it is important to target stress‐response effectors that contribute to in vivo adaptations and associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Since we provide substantial data that this two-component system is important for optimal adaptation, we propose NtrBC should be considered as a global regulatory system that contributes to the physiological balance of P. aeruginosa particularly during infection and complex adaptive lifestyles. Although NtrBC deficiency does not decrease overall bacterial load in the abscess, we know that interefering with stress-response effector proteins provide a means of dismantling bacterial virulence for treating infectious disease in combination with conventional antibiotics (Alford et al, 2019). Further, we previously showed that a broad range of pathogens can be targeted and sensitized to conventional antibiotic therapy in our cutaneous model of high-density bacterial infection by attacking stringent stress response using novel synthetic peptides (Mansour et al, 2016;Pletzer et al, 2017;Pletzer and Hancock, 2018).…”
Section: Resultsmentioning
confidence: 91%
“…Since we provide substantial data that this two-component system is important for optimal adaptation, we propose NtrBC should be considered as a global regulatory system that contributes to the physiological balance of P. aeruginosa particularly during infection and complex adaptive lifestyles. Although NtrBC deficiency does not decrease overall bacterial load in the abscess, we know that interefering with stress-response effector proteins provide a means of dismantling bacterial virulence for treating infectious disease in combination with conventional antibiotics (Alford et al, 2019). Further, we previously showed that a broad range of pathogens can be targeted and sensitized to conventional antibiotic therapy in our cutaneous model of high-density bacterial infection by attacking stringent stress response using novel synthetic peptides (Mansour et al, 2016;Pletzer et al, 2017;Pletzer and Hancock, 2018).…”
Section: Resultsmentioning
confidence: 91%
“…Since virulence factor production is a key determinant of P. aeruginosa pathogenesis ( Alford et al., 2019 , Strateva and Mitov, 2011 ), and NtrBC directly impacted on the levels of secreted virulence factors including cytotoxins like elastase ( Figure 5 ) and rhamnolipids ( Alford et al., 2020 ), we studied whether NtrBC modulated host-directed cytotoxicity in response to in vitro infection ( Figure 6 ). A modest but non-significant increase in cytotoxicity of HBE cells was observed following infection with Δ ntrB or Δ ntrC (13.2% and 7.03% greater than WT, respectively) at an MOI = 1, and a modest but significant 21.5% increase in cytotoxicity was observed following infection with Δ ntrBC .…”
Section: Resultsmentioning
confidence: 99%
“…This effect could be mitigated by complementation of the ntrBC coding region back into mutants ( Figure S2 ). This contributes to our understanding of the complex physiological processes assumed by bacteria during infection that impacts pathogenesis and antimicrobial intervention ( Alford et al., 2019 ) and indicates that NtrBC is important for metabolic adaptation in the nasal cavity and lungs, but not the skin. This data also implicates NtrBC in recurrent CF infection, since P. aeruginosa may persist in the sinus cavity of patients, representing a reservoir where it can adapt and disseminate into the lower respiratory tract over time ( Fothergill et al., 2014 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Preventing bacteria from adapting to their environment can make them vulnerable to antibiotic treatment and clearance by the immune system [ 48 , 49 ]. As a complex and tightly regulated lifestyle adaptation, swarming motility confers fitness in situ by promoting mucosal surface colonization, dissemination to distal tissues [ 11 ], and antibiotic resistance [ 37 ], which can be blocked by 1018 treatment.…”
Section: Discussionmentioning
confidence: 99%